Targeted Myostatin Gene Editing in Multiple Mammalian Species Directed by a Single Pair of TALE Nucleases - Li Xu; Piming Zhao; Andrew Mariano; Renzhi Han (Elsevier, 2013)
Myostatin (MSTN) is a negative regulator of skeletal muscle mass. Strategies to block myostatin signaling pathway have been extensively pursued to increase muscle mass in various disease settings including muscular dystrophy. Here, we report a new class of reagents based on transcription activator-like effector nucleases (TALENs) to disrupt myostatin expression at the genome level. We designed a pair of MSTN TALENs to target a highly conserved sequence in the coding region of the myostatin gene. We demonstrate that codelivery of these MSTN TALENs induce highly specific and efficient gene disruption in a variety of human, cattle, and mouse cells. Based upon sequence analysis, this pair of TALENs is expected to be functional in many other mammalian species. Moreover, we demonstrate that these MSTN TALENs can facilitate targeted integration of a mCherry expression cassette or a larger muscular dystrophy gene (dysferlin) expression cassette into the MSTN locus in mouse or human cells. Therefore, targeted editing of the myostatin gene using our highly specific and efficient TALEN pair would facilitate cell engineering, allowing potential use in translational research for cell-based therapy.